Prospects of senna cultivation in India - Polaiah, A C; N, Khadke G; Bagul, Samadhan Y; Das, Manish (Indian Horticulture, 2023)
The scenario of senna cultivation in the arid and semi-arid regions of India has been discussed in this article. Senna is a rainfed crop and it can tolerate drought conditions and requires low inputs for its cultivation. The requirement of soil and climatic conditions, available varieties to the farmers, land preparation, propagation, sowing season, cultural practices, pest and disease management, harvesting, post-harvest processing, yield, its medicinal properties, marketing and export potential of senna are detailed in this article.